Exploiting the aiming beam to increase the safety of laser lithotripsy: Experimental evaluation of light reflection and fluorescence. Issue 5 (11th September 2019) - Lange, Birgit; Cordes, Jens; Brinkmann, Ralf
Abstract : Background and Objectives: In Holmium laser lithotripsy, usually, the surgeon is guided by a visible beam superimposing the infrared (IR) treatment radiation. It has been shown that a green aiming beam excites stone autofluorescence. This fluorescence signal can be used for calculi detection to check the correct fiber position before triggering the IR laser, thus preventing damage to soft tissue and application devices. However, also the directly reflected green light from the fiber tip gives valuable information on fiber position and its surface condition. Materials and Methods: An external fiber‐fiber‐coupling‐box (fiber core diameter 365 µm) for pulsed holmium laser radiation (2.1 µm) was set up containing a green diode laser module (520 nm, average power on the sample <0.5 mW) and optics and detectors for measuring the reflected light of this aiming beam as well as the fluorescence excited with it. Measurements were done via a lock‐in technique with more than 20 human calculi samples and porcine calix in vitro . After the implementation of automatic data storage signals during ongoing in vitro lithotripsy procedures were recorded with the fiber positioned on tissue, stone, or in/on medical equipment (working channel of an endoscope, stone retrieval basket). Results: Stone fluorescence signals measured were a factor of 7 to >100 higher than those of tissue. Stone fluorescence was detectable in "non‐contact mode" with a linear signal decrease over a distance up to ~1 mm in front of the fiber tip (core diameter 365 µm) and with severely damaged fibers (max. decrease: 75% with pinched off fiber). Reflection signals of the fiber tip surface in air and water surrounding decreased significantly when the fiber was damaged; measured ratios of intact to damaged fiber found in the air were (5–17):1 and in water (1.6–3.7):1. Surfaces in front of the fiber aggravated the evaluation of fiber condition due to reflections but enabled to detect, for example, the working channel of a flexible endoscope in combination with the (missing) fluorescence signal. Conclusions: Autofluorescence induced by a green aiming beam can be exploited for stone detection in laser lithotripsy. A reflection measurement can give further information on fiber condition and position. Implementing this kind of safety features for an automatic block of IR laser emission in case of weak or missing fluorescence and un‐normal reflections can assist the surgeon by avoiding tissue perforation, and damage to medical devices such as endoscopes. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.